Percutaneous Rheolytic Thrombectomy of Thrombosed Autogenous Dialysis Fistulas: Technical Results, Clinical Outcome, and Factors Influencing Patency. (February 2015) - Maleux, Geert; De Coster, Bruno; Laenen, Annouschka; Vaninbroukx, Johan; Meijers, Björn; Claes, Kathleen; Fourneau, Inge; Heye, Sam
Purpose: To retrospectively analyze the technical and clinical outcome of percutaneous rheolytic thrombectomy with the use of the AngioJet device in thrombosed autogenous arteriovenous dialysis fistulas.Methods: A cohort of 38 consecutive patients (24 men; mean age 70.7±13.8 years) presenting with 59 thrombotic events in 39 autogenous dialysis fistulas were retrospectively analyzed. The AngioJet rheolytic thrombectomy device was used in all cases. Adjunctive therapies, as well as procedure-related complications, were noted. Primary, assisted primary, and secondary patency of the autogenous fistulas was assessed along with factors potentially influencing patency.Results: Initial technical success to recanalize the efferent vein was 100% (n=59), and a successful postprocedure dialysis session was possible in 97% (n=57) of cases. Adjunctive procedures included percutaneous thromboaspiration (n=4, 7%), balloon angioplasty (n=59, 100%), and stent placement (n=16, 27%). Complications related to thrombectomy occurred in 3 (5%) procedures (distal arterial embolus). Primary, assisted primary, and secondary patency rates at 12 months were 56.1% (95% CI 42.8% to 75.2%), 61.6% (95% CI 48.6% to 74.7%), and 86.2% (95% CI 74.9% to 97.5%), respectively. Risk factors for early fistula occlusion were greater patient age (p=0.045), the age of the fistula (p=0.045), previous stent insertion (p=0.019), and an upper arm fistula (p=0.047).Conclusion: Percutaneous rheolytic thrombectomy of autogenous dialysis fistulas is effective in restoring patency and allowing subsequent hemodialysis. The complication rate is acceptably low, and the large majority of the fistulas are still used for hemodialysis at 1-year follow-up. Older fistulas and upper arm fistulas are at higher risk for early rethrombosis.